2023
DOI: 10.1097/dbp.0000000000001182
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Trial of a Peer-to-Peer Psychoeducational Intervention for Parents of Black Children Awaiting a Developmental Evaluation

Abstract: Objective:This study examined the short-term impact on child, family, and parent outcomes of a peer-to-peer psychoeducational intervention, Parents Taking Action (PTA) for Black families of children awaiting developmental-behavioral pediatric evaluations.Methods:We targeted parents and other primary caregivers of Black children aged 8 years or younger awaiting a developmental or autism evaluation at an academic tertiary care hospital. Using a single-arm design, we recruited participants directly from the appoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A total of 5078 studies were identified, imported into EXCEL and full texts read for relevance (n=93), if not relevant the reason for exclusion was noted (see figure 1), 18 papers were identified as meeting the eligibility criteria. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The characteristics of the 18 included studies are presented in online supplemental table 2 and online supplemental table A1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5078 studies were identified, imported into EXCEL and full texts read for relevance (n=93), if not relevant the reason for exclusion was noted (see figure 1), 18 papers were identified as meeting the eligibility criteria. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The characteristics of the 18 included studies are presented in online supplemental table 2 and online supplemental table A1.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, parents in this study made it clear that they would benefit from parent support and parent-mediated interventions. Parent training is an accessible method for promoting long-term behavioral improvements among children with autism (Bearss et al, 2015; Dababnah et al, 2023). Care providers within rural communities should consider providing knowledge-focused and technique-focused parent training as a psychotherapeutic intervention in which clinicians teach parents effective skills.…”
Section: Discussionmentioning
confidence: 99%
“…To combat service access barriers in rural areas, autism diagnostic and treatment services delivered via telehealth may be a viable option (de Nocker & Toolan, 2021; Wagner et al, 2021). Targeted parent training on autism information, tools, and resources may be another way to improve access to services for families in rural areas (Dababnah et al, 2023). Bearss et al (2015) defined a taxonomy for parent training programs in the following two categories: (a) parent support, which is knowledge-focused (i.e., child is an indirect beneficiary) and includes psychoeducation and care coordination, and (2) parent-mediated intervention, which is technique-focused (i.e., child is the direct beneficiary) and includes interventions for core symptoms and maladaptive behaviors.…”
mentioning
confidence: 99%